Legal Analysis of Universitas Wijaya Kusuma Surabaya Tower II Building Construction Agreement Between Wijaya Kusuma Foundation and PT Sinar Waringin Adikarya - Sulistiyo, Sulistiyo (Universitas Wijaya Kusuma Surabaya, 2021)
In this study, researchers used the title Legal Analysis the Implementation of the Tower II Building Construction Agreement Wijaya Kusuma Surabaya University with PT SINAR WARINGIN ADIKARYA. This research was conducted To find out and analyze: Rights and Obligations of each party in the Towering Contract (Construction Contract) of Tower II Building, Universitas Wijaya Kusuma Surabaya, the form of the responsibilities of each party in the contracting contract (Construction Contract) Tower II Building, Universitas Wijaya Kusuma Surabaya, if one party makes a mistake. From the results of the analysis conducted in this study, the researcher states that: Rights and obligations must be carried out by each party as stated in the work implementation agreement as contained in Attachment to the work implementation agreement Number: 597/WK/XII/2017, as stated in Article 3 of the agreement when referred to as a second party's obligation it means the right of the first party, among others, to carry out the work carefully, accurate and complete responsibility by providing experts and other personnel, materials, equipment needed for the implementation of the work. The responsibilities that must be carried out in this work implementation agreement must be guided by the provisions of the agreement as referred to in the Attachment to the work implementation agreement Number: 597/WK/XII/2017, namely contained in article 4, article 6, article 7, article 8, and article 11.Keywords: Agreement; Construction; University